2019
DOI: 10.1136/bmjgh-2018-001134
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the information deficit in global health: lessons from a digital acute care platform in Sri Lanka

Abstract: Lack of investment in low-income and middle-income countries (LMICs) in systems capturing continuous information regarding care of the acutely unwell patient is hindering global efforts to address inequalities, both at facility and national level. Furthermore, this of lack of data is disempowering frontline staff and those seeking to support them, from progressing setting-relevant research and quality improvement. In contrast to high-income country (HIC) settings, where electronic surveillance has boosted the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 28 publications
0
48
0
Order By: Relevance
“…29 The benefits and challenges associated with collection of healthcare data using mobile technology have been previously discussed. 30,31 Benefits include a decentralized approach to collection of data from the 95% of the global population living in an area covered and subscribed to mobile cellular service. 32 Specifically in LMIC, there were 5.5 billion mobile phone subscriptions, representing nearly 92 subscriptions per 100 inhabitants.…”
Section: Discussionmentioning
confidence: 99%
“…29 The benefits and challenges associated with collection of healthcare data using mobile technology have been previously discussed. 30,31 Benefits include a decentralized approach to collection of data from the 95% of the global population living in an area covered and subscribed to mobile cellular service. 32 Specifically in LMIC, there were 5.5 billion mobile phone subscriptions, representing nearly 92 subscriptions per 100 inhabitants.…”
Section: Discussionmentioning
confidence: 99%
“…This study uses a recently implemented electronic AMI registry, codesigned by clinicians of the Sri Lanka STEMI Forum, with the purpose of enabling prospective systematic evaluation of care for patients with AMI. Using the Network for Improving Critical care Systems and Training (NICST) methodology, the registry uses a mobile platform with capacity for real-time visualisation of routine information (including referral, diagnosis and management) 5 10. The same platform facilitates evaluation of patient-reported outcomes: satisfaction, functional recovery and burden of symptoms following discharge.…”
Section: Methodsmentioning
confidence: 99%
“…Digital surveillance systems capable of replicable and continuous evaluation of care that can be embedded within healthcare delivery remain notably absent in many LMICs. However, recent efforts have shown that such systems are both feasible and can help guide priorities for care improvement 8–10…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the rapid spread of internet-enabled mobile devices has facilitated data collection and allowed for the expansion of clinical registries, providing clinicians with data to drive local quality improvement and researchers with aggregated data to inform policy. Future work needs to concentrate on ensuring consistent definitions and data fields to limit redundancy and to maximise collaboration 28 29…”
Section: Need Access and Qualitymentioning
confidence: 99%